Cytomorphology of Circulating Colorectal Tumor Cells:A Small Case Series. (30th November 2009) - Marrinucci, Dena; Bethel, Kelly; Lazar, Daniel; Fisher, Jennifer; Huynh, Edward; Clark, Peter; Bruce, Richard; Nieva, Jorge; Kuhn, Peter
Abstract : Several methodologies exist to enumerate circulating tumor cells (CTCs) from the blood of cancer patients; however, most methodologies lack high-resolution imaging, and thus, little is known about the cytomorphologic features of these cells. In this study of metastatic colorectal cancer patients, we used immunofluorescent staining with fiber-optic array scanning technology to identify CTCs, with subsequent Wright-Giemsa and Papanicolau staining. The CTCs were compared to the corresponding primary and metastatic tumors. The colorectal CTCs showed marked intrapatient pleomorphism. In comparison to the corresponding tissue biopsies, cells from all sites showed similar pleomorphism, demonstrating that colorectal CTCs retain the pleomorphism present in regions of solid growth. They also often retain particular cytomorphologic features present in the patient's primary and/or metastatic tumor tissue. This study provides an initial analysis of the cytomorphologic features of circulating colon cancer cells, providing a foundation for further investigation into the significance and metastatic potential of CTCs.